-6(4d+10)+7d=-2d

Simple and best practice solution for -6(4d+10)+7d=-2d equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(4d+10)+7d=-2d equation:


-6(4d+10)+7d=-2d

We simplify the equation to the form, which is simple to understand
-6(4d+10)+7d=-2d

Reorder the terms in parentheses
+(-24d-60)+7d=-2d

Remove unnecessary parentheses
-24d-60+7d=-2d

We move all terms containing d to the left and all other terms to the right.
-24d+7d+2d=+60

We simplify left and right side of the equation.
-15d=+60

We divide both sides of the equation by -15 to get d.
d=-4

See similar equations:

| 5+7x-5x=3 | | -x-4+2x=-5 | | 2x-6+2x=14 | | 3/5(x+1)=1/15(x+2) | | (-4)(6)(-7)= | | 4x+7-2x=5 | | 4(2x-1)/5(x-3) | | 16-20-(-8)-9= | | 4x-1+7x=-89 | | 15b-1=30 | | (4x-3)2=36 | | 12-4x+6+x=-3 | | X-2+5=6 | | 27=-7x+5x+9 | | x/-4-(-8)=12 | | d^2+8-225=0 | | -130=-7x-5x-10 | | -4x/5+1=7/15 | | 2-7x-3x=-58 | | 196-4x=32x+24 | | -2-3x+2x=6 | | 3(4+1)+6(-3)= | | 45/6 | | -7x+4+6x=-6 | | 6+(-18)+(-13)+9= | | -6.5+d=72 | | 504=7*8x | | x/9=100 | | =(3x-4)(3x-4)+6 | | f/3=-3 | | x/-3=-15 | | 10+3x-2x=12 |

Equations solver categories